Motif Penggunaan Fitur Stories Highlight Instagram sebagai Memori Media bagi Generasi Milenial - Nabila Putri Aldira (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
The evolution of information and communication technology has brought changes to the way people perceive things. The presence of new media (digital) has eroded analog media. Modern society has switched to practical and dynamic digital use. The form of communication and memory storage or past memories also changes to become digitalized. This study aims to know and explore about motives for using Instagram stories highlight feature as a form of media memory for the millennial generation. This study uses the phenomenological theory of Alfred Schütz, the concept of new media, Instagram and the concept of media memory. By using the interpretive paradigm, qualitative approach, phenomenological research methods and descriptive research design, this study found that there are because-motives and in-order-to motives. The result of because motives (because-motives) in using Instagram highlight stories for millennial generation, are caused by following friends and trends, because it takes advantage of new media technology, and because Instagram highlight stories feature has more interesting options to convey messages and save memories than other features. There are also results about in-order-to motives in using Instagram highlight stories for millennial generation, to form a conceptual and structured digital album, in order to show off to others, and to be grateful for experiences that have happened in the future. And there are also found a result about the meaning of using Instagram stories highlight feature for millennial generation, as a digital album to store memories that have happened in the past. The conclusion is, Instagram highlight stories for millennial generation is a way of communicating through digital albums as an introduction to messages to other people in the modern era.